KAJIAN STILISTIKA SASTRA SULUK PEDALANGAN KI SENO NUGROHO LAKON SÃTA GUGUR - , BRIAN RIANGGA DHITA; , Dr. Wisma Nugraha Christianto, Rich, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The suluk pedalangan is one form of Javanese literature that has characteristics of typical disclosure, puitic, to giving literary of value. The one beauty of shadow puppet theatre reflected in language style use. The language on the suluk pedalangan dissimilar to colloquial language, because most use old Javanese language. Based on the study of Javanese literature stylistic, this research aims to describe and explain aspects of language that use on the suluk pedalangan of shadow puppet theatre by Ki Seno Nugroho in the death of Séta performance.The study of Javanese literature stylistic from this research to be divided into three main topics based on the study of Javanese literature stylistic accordance with the S.Padmosoekotjo idea, that is language style, diction, and aspects of sound. The result from this research shows that language style which are found on the suluk pedalangan of shadow puppet by Ki Seno Nugroho in the death of Séta performance is pepindhan, tembung éntar and tembung saroja. As for the diction that found on the suluk pedalangan of shadow puppet by Ki Seno Nugroho in the death of Séta performance is tembung plutan, tembung garba, and dasanama. The analysis from the aspects sound for this research among them are purwakanthi guru swara, purwakanthi guru sastra, and purwakanthi lumaksita. The function of language style, diction and aspects of sound from this suluk pedalangan of shadow puppet theatre by Ki Seno Nugroho in the death of Séta performance as trimmer sulukan and giving the assertion effect about events or figure which was presented in the show. Keywords: Javanese stylistic, suluk pedalangan, shadow puppet, the death of Séta, Padmosoekotjo